2016
DOI: 10.1590/1678-457x.16116
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mineral content and heavy metals of dromedary camel milk in Iran

Abstract: The aim of this study was to determine the amount of major mineral compounds and heavy metals of camel milk in Iran. For this purpose camel milk samples were collected from seven regions of Iran include Qazvin, Golestan, Semnan, Sistan-Baluchestan, Khuzestan, Bushehr and Tehran. The samples were analyzed using Inductively Coupled Plasma-Optical Emission Spectrometer (ICP-OES) method. The results showed that among the mineral contents, iron and zinc of camel milk were greater than bovine milk. Based on the code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…Our results showed the values of lead in the cow milk samples were in agreement with those reported from Turkey (Simsek et al, 2000;Ayar et al, 2009), Croatia (Pavlovic et al, 2004;Bilandzic et al, 2011), and several times higher than those reported from India (Tripathi et al, 1999;Dhanalakshmi and Gawdaman, 2013), Thailand (Parkpian et al, 2003), Italy (Licata et al, 2004), South Africa (Ataro et al, 2008), Spain (Gonzalez-Montaña et al, 2012), Greece (Gougoulias et al, 2014), and Iran (Najarnezhad and Akbarabadi, 2013;Najarnezhad et al, 2015;Mostafidi et al, 2016). Although they are inferior, to those investigated in Italy (Coni et al, 1995;Caggiano et al, 2005;Anastasio et al, 2006), India (Swarup et al, 2005), Romania (Serdaru et al, 2001),…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results showed the values of lead in the cow milk samples were in agreement with those reported from Turkey (Simsek et al, 2000;Ayar et al, 2009), Croatia (Pavlovic et al, 2004;Bilandzic et al, 2011), and several times higher than those reported from India (Tripathi et al, 1999;Dhanalakshmi and Gawdaman, 2013), Thailand (Parkpian et al, 2003), Italy (Licata et al, 2004), South Africa (Ataro et al, 2008), Spain (Gonzalez-Montaña et al, 2012), Greece (Gougoulias et al, 2014), and Iran (Najarnezhad and Akbarabadi, 2013;Najarnezhad et al, 2015;Mostafidi et al, 2016). Although they are inferior, to those investigated in Italy (Coni et al, 1995;Caggiano et al, 2005;Anastasio et al, 2006), India (Swarup et al, 2005), Romania (Serdaru et al, 2001),…”
Section: Discussionsupporting
confidence: 91%
“…Spain (Sola-Larrañaga and Navarro-Blasco, 2009), France (Maas et al, 2011), Sudan (Abdalla et al, 2013), Iran (Najarnezhad and Akbarabadi, 2013;Mostafidi et al, 2016) and Pakistan (Batool et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Higher concentrations of toxic heavy metals in spring milk may be due to the differences in feeding patterns of dairy animals in Iran, differences in the amount of soil ingested by animals and vegetation types in different seasons, differences in the amounts of rainfall in various seasons and finally using chemical Table 4. Standard allowed limit concentrations of Cd, Pb and Hg in milk samples [13][14][15][16][17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the recent researches on dairy technology, science and nutrition (Akal & Yetişemiyen, 2016;Barbosa et al, 2013;Bosso et al, 2016;Hamoudi-Belarbi et al, 2016;Mostafidi et al, 2016;Rangel et al, 2016;Sales et al, 2016), there are few information's published on the sweetened condensed milk subject.…”
Section: Introductionmentioning
confidence: 99%